PERBANDINGAN KADAR LOGAM KADMIUM (Cd) DALAM DARAH PEROKOK AKTIF DAN PASIF DI TERMINAL BUS - Rosita, Betti; Andriyati, Fadhlika (Sainstek : Jurnal Sains dan Teknologi, 2019)
The high number of smokers in Indonesia is caused by uncontrolled circulation of cigarettes. The danger of smoking does not only occur in active smokers, but also is harmful to passive smokers. Cadmium (Cd) is one of the metals contained in cigarettes that have high toxicity. Cadmium (Cd) is transported in the blood which binds to red blood cells and high molecular weight proteins in the plasma, especially by albumin. The purpose of this study was to determineathe ratio of metal levels of Cadmium (Cd) in the blood of active and passive smokers. Determination of metal content in blood samples by wet destruction method was then analyzed by Atomic Absortion Spectrophotometer (AAS). This type of research is experiment. Based on the results of the study, the lowest ratio of cadmium (Cd) in the blood of active smokers was 0.8 g / dL and the highest level was 1.6 g / dL while the lowest metal level in the blood of passive smokers was 0.8 g/ dL and the highest level is 1.4 g / dL, the highest metal content in the blood of the smoker shows a value that exceeds the normal threshold. From the statistic test, the value of 0.413 was obtained so that P>0.05 so that Ho was accepted, this showed that there was no significant difference between cadmium (Cd) levels in the blood of active smokers and passive smokers in the bus terminal.